2013
DOI: 10.1590/s0100-06832013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Potential acidity estimated by SMP pH in soils of the state of Pará

Abstract: SUMMARY RESUMO: ACIDEZ POTENCIAL ESTIMADA PELO MÉTODO DO pH SMP EM SOLOS DO ESTADO DO PARÁ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…Therefore, several studies in Brazil have sought to estimate the levels of H + Al using the method developed by Shoemaker, McLean, and Pratt (SMP) (Shoemaker;Mclean;Pratt, 1961). Numerous authors have developed regression equations to estimate the H + Al values in some Brazilian states and concluded that the SMP method is easy to perform and produces estimates showing an excellent correlation with the H + Al content extracted using the calcium acetate method (Almeida Júnior et al, 2015;Araújo et al, 2014;Escosteguy;Bissani, 1999;Gama et al, 2013;Maeda et al, 1997;Moreira et al, 2004;Pavan;Oliveira;Miyazawa, 1996;Santanna et al, 2011;Sousa et al, 1989;Steiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies in Brazil have sought to estimate the levels of H + Al using the method developed by Shoemaker, McLean, and Pratt (SMP) (Shoemaker;Mclean;Pratt, 1961). Numerous authors have developed regression equations to estimate the H + Al values in some Brazilian states and concluded that the SMP method is easy to perform and produces estimates showing an excellent correlation with the H + Al content extracted using the calcium acetate method (Almeida Júnior et al, 2015;Araújo et al, 2014;Escosteguy;Bissani, 1999;Gama et al, 2013;Maeda et al, 1997;Moreira et al, 2004;Pavan;Oliveira;Miyazawa, 1996;Santanna et al, 2011;Sousa et al, 1989;Steiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O valor obtido corresponde ao valor do pH de equilíbrio obtido na suspensão entre o solo e a solução-tampão SMP. Vários estudos comprovam a eficiência do método em diversas regiões do Brasil (Pavan et al, 1996;Pereira et al, 1998;Escosteguy e Bissani, 1999;Nascimento, 2000;Kaminski et al, 2002;Sambatti et al, 2003;Moreira et al, 2004;Pereira et al, 2006;Silva et al, 2006;Chaves et al, 2007;Silva et al, 2006;Moline et al, 2011;Gama et al, 2013) e também corroboram a necessidade de trabalhos regionalizados para adequar o uso da solução SMP para estimativa da acidez potencial (Pavan et al 1996;Nascimento, 2000;Quaggio e Raij, 2001), dada a grande variabilidade de solos no país.…”
Section: Introductionunclassified
“…A estimativa da acidez potencial pelo uso do pH(SMP) deve ser ajustada por região, buscando-se encontrar equações que expressem essa relação de modo satisfatório em virtude das variações encontradas entre tipos de solo (Pereira et al, 1998;Escosteguy e Bissani, 1999;Gama et al, 2013). Um motivo também para definir uma equação que relaciona o teor de H+Al com o pH(SMP), para solos ou regiões ainda não incluídos nesses estudos, seria o crescente interesse na utilização do método da saturação de bases para estimar a necessidade de calagem, o qual exige a determinação dos teores de H+Al nas análises de rotina (Wiethölter, 1997;Kaminski et al, 2002 O modelo quadrático foi o que melhor se ajustou entre as variáveis (Figura 2).…”
Section: Introductionunclassified
See 2 more Smart Citations